Platelet to Lymphocyte Ratio and Neutrophil to Lymphocyte Ratio in Missed Abortion - Ismail Biyik; Mustafa Albayrak; Fatih Keskin (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective Missed abortion occurs in ~ 15% of all clinical pregnancies. The pathogenesis is not clearly known. However, defective placentation resulting in maternal systemic inflammatory response is considered responsible for missed abortion. Platelet lymphocyte ratio (PLR) and neutrophil lymphocyte ratio (NLR) are increasingly cited parameters of inflammation in the literature. However, no study evaluated the PLR and NLR rates in missed abortions so far. The aim of the present study is to investigate whether complete blood count (CBC) inflammatory parameters such as NLR and PLR are increased in patients with missed abortion. Methods Medical records of 40 pregnant women whose gestation ended in missed abortion at between 6 and14 weeks of gestation and of 40 healthy pregnant women were collected and compared retrospectively. The groups were compared regarding hemoglobin, hematocrit, platelet count (PLT), mean platelet volume (MPV), platelet distribution width (PDW), PLR and NLR. Results Platelet distribution width, NLR and PLR values were higher in the missed abortion group compared with the healthy pregnant women group (rates are p = 0.043; p = 0.038; and p = 0.010, respectively). Hematocrit, MPV, and lymphocyte values were found to be lower in the missed abortion group compared with the healthy pregnant women group (p = 0.027, p = 0.044 and p = 0.025, respectively). Conclusion The PDW, NLR and PLR values of the missed abortion group were reported high; and MPV values were reported low in the present study. These ﬁndings may help to speculate a defective placentation in the pathogenesis of missed abortion.